Mindfullness Spiritual Islami untuk Meningkatkan Kesejahteraan Spiritual Lansia dengan Hipertensi - Nina Gartika; Anggriyana Tri Widianti; Inggriane Puspita Dewi; Silfia Ajeng Wulandari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of an Islamic spiritual mindfulness intervention on the spiritual well-being of older adults with hypertension. The method used was a pre-experimental, one-group, pre- and post-test design without a control group. The results showed that the majority of respondents were aged 69–73 years (53.3%), almost all were female (93.3%), most had a primary school education (53.3%), were widowed (53.3%), and nearly all were unemployed (housewives) (86.7%). Most respondents' spiritual well-being before the intervention (60%) was in the low category, and after the intervention, most (66.7%) were in the high category. Statistical tests showed a significant effect of the Islamic spiritual mindfulness intervention on spiritual well-being among older adults. In conclusion, 15 minutes of Islamic spiritual mindfulness can be implemented as part of an independent nursing intervention to improve the spiritual well-being of older adults with hypertension. Keywords: Hypertension, Spiritual Well-being, Elderly, Islamic Spiritual Mindfulness